The Marco Gonzalez Maya site, Ambergris Caye, Belize: Assessing the impact of human activities by examining diachronic processes at the local scale. (5th May 2017) - Graham, Elizabeth; Macphail, Richard; Turner, Simon; Crowther, John; Stegemann, Julia; Arroyo-Kalin, Manuel; Duncan, Lindsay; Whittet, Richard; Rosique, Cristina; Austin, Phillip
Abstract: Research at the Maya archaeological site of Marco Gonzalez on Ambergris Caye in Belize is socio-ecological because human activities have been a factor in the formation and fluctuation of the local marine and terrestrial environments over time. The site is one of many on Belize's coast and cayes that exhibit anomalous vegetation and dark-coloured soils. These soils, although sought for cultivation, are not typical 'Amazonian Dark Earths' but instead are distinctive to the weathering of carbonate-rich anthropogenic deposits. We tentatively term these location-specific soils as Maya Dark Earths. Our research seeks to quantify the role of human activities in long-term environmental change and to develop strategies, specifically Life Cycle Assessment (LCA), that can be applied to environmental impact modelling today.